Role of Supervisor Behavioral Integrity for Safety in the Relationship Between Top-Management Safety Climate, Safety Motivation, and Safety Performance - Mehmet Peker; Onur C. Doğru; Gülgün Meşe (Elsevier, 2022)
Background: This study examines whether employee perceptions of supervisor behavioral integrity for safety moderates the relationship between top-management safety climate and safety performance (i.e., safety compliance and safety participation) and the mediated relationships through safety motivation. Methods: Data collected from 389 blue-collar employees were analyzed using latent moderated structural equation modeling. Results: The results indicate that the relationship between top-management safety climate and safety behavior, and the mediating role of safety motivation were replicated. Moreover, the results show that the mediated relationships between top-management safety climate and safety behaviors through safety motivation were stronger for employees who report high supervisor behavioral integrity for safety. Conclusion: The study findings suggest the role of supervisor behavioral integrity for safety in clarifying how the employee perceptions of top-management safety climate transfer to the employee safety behaviors through the motivational pathway.